2018
DOI: 10.5530/jyp.2018.10.101
|View full text |Cite
|
Sign up to set email alerts
|

Use of Anti-Inflammatory Agents by Pharmacy College Students: Correlation of the Menstrual Cycle and Self-medication

Abstract: Aim: This study aims to evaluate the use of nonsteroidal anti-inflammatory drugs (NSAIDs) and factors associated with this practice as well as drugrelated problems and self-medication by pharmacy students of University Center Catholic of Quixadá, Ceará, Brazil. Methods: The prospective study with a quantitative approach was conducted. The participants were 96 female pharmacy students, who answered an e-mail questionnaire containing questions regarding the main NSAIDs used, pre-menstrual and menstrual use, drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Another study also found that NSAIDs were among the non-prescription or OTC products most commonly used by Malaysian women to counter PMS symptoms, alongside vitamin supplements and health diets [12]. Two other studies highlighted that the drugs chiefly used for PMS were those having analgesic or anti-inflammatory effect [37,38]. There is a psychological need among women to reduce or prevent pain caused by PMS, and this often leads to self-medication [38].…”
Section: The Respondents' Pattern Of Pharmacological Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study also found that NSAIDs were among the non-prescription or OTC products most commonly used by Malaysian women to counter PMS symptoms, alongside vitamin supplements and health diets [12]. Two other studies highlighted that the drugs chiefly used for PMS were those having analgesic or anti-inflammatory effect [37,38]. There is a psychological need among women to reduce or prevent pain caused by PMS, and this often leads to self-medication [38].…”
Section: The Respondents' Pattern Of Pharmacological Recommendationsmentioning
confidence: 99%
“…Two other studies highlighted that the drugs chiefly used for PMS were those having analgesic or anti-inflammatory effect [37,38]. There is a psychological need among women to reduce or prevent pain caused by PMS, and this often leads to self-medication [38]. Overall, health supplements were less frequently used by women with PMS, as those products are not sufficiently rapid-acting to bring about quick symptomatic relief.…”
Section: The Respondents' Pattern Of Pharmacological Recommendationsmentioning
confidence: 99%